Humanistic-Religious Guidance and Reported Spiritual Change among Children in Conflict with the Law in Indonesia - Nisa, Siti Maziatun; Aziz, Abdul (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Guidance for children in conflict with the law must address institutional accountability while recognizing their psychological, educational, and spiritual needs. Previous studies have examined legal protection, counseling, education, and religious programs in juvenile correctional institutions but provide limited explanation of how person-centered relationships and Islamic spiritual practices are combined in everyday guidance. This qualitative single-case study examined the implementation of humanistic-religious guidance at Lembaga Pembinaan Khusus Anak Kelas I Kutoarjo (LPKA Kutoarjo), an Indonesian juvenile correctional institution. It also examined participant-reported changes in spiritual awareness and the conditions supporting or constraining the approach. Data were obtained from five purposively selected participants—three staff members and two participating children—through semi-structured interviews, 15–20 hours of nonparticipant observation over five consecutive days, and institutional document analysis. The analysis identified seven interconnected elements: unconditional acceptance, empathy, congruence, muhasabah (self-reflection), taubat nasuha (sincere repentance), muraqabah (awareness of being observed by God), and ihsan (worship and moral conduct grounded in awareness of God). These elements were expressed across staff–child interactions, reflective activities, religious routines, equivalency education, and digital-library use. The two participating children described emotional-regulation efforts, regular worship, Quranic learning, and participation in scheduled religious activities. Interview accounts identified staff competence, institutional cooperation, and educational facilities as supporting conditions, and varied backgrounds, limited placement periods, reading difficulties, shame, withdrawal, and despair as constraints.